Hematopoietic stem cell transplantation in juvenile myelomonocytic leukemia: analyse one centre experience and literature review - M. A. Maschan; L. A. Khachatryan; Yu. V. Skvortsova; E. E. Kurnikova; D. A. Shasheleva; V. O. Bobrynina; D. N. Balashov; E. V. Skorobogatova; D. D. Baydildina; G. A. Novichkova; A. A. Maschan (Онкогематология, 2014)
Allogeneic hematopoietic stem cell transplantation (HSCT) is the standard curative therapy for juvenile myelomonocytic leukemia (JMML). Seventeen patients with JMML received myeloablative conditioning (busulfan-based — 15, treosulfan-based — 2). Donors included 5 matched related siblings, 8 — matched unrelated volunteer or cord blood (2), 4 — mismatched relatives. Primary engraftment was achieved in 75 %. The rate of acute GVHD grade II–IV was 58 %, grade III–IV — 23 %. Chronic GVHD occurred in 33 % of patients. Five JMML relapses occurred. Relapse-free survival is 66 ± 12 %. Four patients died of transplant-related complications. TRM was 28 ± 12 %.Five patients died of disease progression. Overall survival is 38 ± 13 % with median follow-up of 13 months. A review of most important publications related to HSCT in JMML is provided.